Review for Collective Problem-Solving by a Group of Robots (Journal of Universal Science Research, 2024)
This article discusses the relevance of using a group of robots to solve various problems. It was also revealed that despite the obvious advantages of this approach, it causes certain problems in its implementation. The authors address some of these problems and offer possible solutions to them.